DL0410 Alleviates Memory Impairment in D-Galactose-Induced Aging Rats by Suppressing Neuroinflammation via the TLR4/MyD88/NF-κB Pathway. (5th October 2021) - Zhang, Baoyue; Lian, Wenwen; Zhao, Jun; Wang, Zhe; Liu, Ailin; Du, Guanhua
Abstract : Oxidative stress and neuroinflammation have been demonstrated to be linked with Alzheimer's disease (AD). In this study, we examined the protective effects of DL0410 in aging rats and explored the underlying mechanism against oxidative damage and neuroinflammation, which was then validated in LPS-stimulated BV2 microglia. We firstly investigated the improvement effects of DL0410 on learning and memory abilities and explored the potential mechanisms in D-gal-induced aging rats. An 8-week treatment with DL0410 significantly improved the learning and cognitive function of D-gal-stimulated Alzheimer's-like rats in the Morris water maze test, step-down test, and novel object recognition test, and the therapeutic effect of DL0410 at 10 mg/kg was even better than that of donepezil. What is more, the results showed that DL0410 alleviated neuron injury, increased the number of synapses, and improved the level of postsynaptic density protein 95 (PSD95) in the hippocampus and cortex. Next, we examined the protective effects of DL0410 against oxidative damage and neuroinflammation. Our observations indicated that DL0410 reduced the production of harmful oxidation products and promoted the antioxidative system, decreased the levels of proinflammatory cytokines, including tumor necrosis factor α (TNF- α ), interleukin 1 β (IL-1 β ), and interleukin 6 (IL-6), and increased anti-inflammatory cytokines IL-10. Moreover, DL0410 inhibited the activation of astrocytes and microglia and suppressed the activation of the TLR4/MyD88/NF- κ B signaling pathway. The anti-inflammation effect of DL0410 was further confirmed in LPS-stimulated BV2 cells, and the results showed that DL0410 reduced the level of inflammatory factors and inhibited the activation of the TLR4/MyD88/TRAF6/NF- κ B signaling pathway in BV2 microglia. Molecular docking results indicated that DL0410 occupied the LPS recognition site in the TLR4/MD2 complex. Furthermore, the enhanced expression of claudin-1, claudin-5, occludin, CX43, and ZO-1 indicated that DL0410 protected the blood-brain barrier (BBB) integrity. Together, these results suggest that DL0410 exerts neuroprotective effects against hippocampus and cortex injury induced by D-galactose, and the possible mechanisms include antioxidative stress, antineuroinflammation, improving synaptic plasticity, and maintaining BBB integrity, which is mediated by the TLR4/MyD88/NF- κ B signaling pathway inhibition. We suggest that DL0410 is a promising candidate for AD treatment.